2020
DOI: 10.3390/ijms21051830
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Aging in Skeletal Muscle Regeneration and Disease

Abstract: Skeletal muscle comprises 30–40% of the weight of a healthy human body and is required for voluntary movements in humans. Mature skeletal muscle is formed by multinuclear cells, which are called myofibers. Formation of myofibers depends on the proliferation, differentiation, and fusion of muscle progenitor cells during development and after injury. Muscle progenitor cells are derived from muscle satellite (stem) cells (MuSCs), which reside on the surface of the myofiber but beneath the basement membrane. MuSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 161 publications
1
75
0
1
Order By: Relevance
“…Skeletal muscle comprises approximately 40% of the total body weight. Maintenance of skeletal muscle homeostasis is essential for maintaining the body's various functions (Ferreira et al, 2019;Yamakawa et al, 2020). An imbalance in skeletal muscle homeostasis can cause skeletal muscle hyperplasia or atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle comprises approximately 40% of the total body weight. Maintenance of skeletal muscle homeostasis is essential for maintaining the body's various functions (Ferreira et al, 2019;Yamakawa et al, 2020). An imbalance in skeletal muscle homeostasis can cause skeletal muscle hyperplasia or atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is a major risk factor for impaired muscle healing due to tissue fibrosis. Several studies at the cellular and molecular level have examined age‐related differences in muscle healing potential and have identified an age‐related decline in the potency of muscle progenitor cells (MPCs) 44‐46 . It has been reported that exposure to some factors present in the serum of young mice by heterochronic parabiosis (connecting the circulatory systems of a young and an old mouse) can restore the activation of Notch signaling as well as the proliferation and regenerative capacity of aged satellite cells 47 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the capacity to reach this adaptation is almost intact in aged human skeletal muscle [ 55 ]. This is of importance as muscle regenerative capacity is impaired in aged skeletal muscle [ 56 ]. Therefore, aged skeletal muscle cells show a low renewal rate but almost intact mitochondrial function (at least in response to exercise) which somewhat mimics the physiology of cardiomyocytes [ 57 ].…”
Section: The Mitochondria–macrophage Connection Regulates Metabolimentioning
confidence: 99%